Perancangan Video Infografis Animasi Interaktif tentang Prosedur Pemberangkatan Tenaga Kerja Indonesia Berbasis Android - Adelita Arinata; T.Arie Setiawan (Maranatha University Press, 2017)
This study discusses the making of the animated infographics videos interactive which is based on the problem towards labour workers of Indonesia due to the low level of education and knowledge that causing fraud and human trafficking. With this following issues, there is a need of socialization media and information for the labour workers. This design is made with mixed method and linear strategies. The final result of this design is an animated infographics video that can be accessed through Android smartphone which is used as information and socialization media for labour workers in Indonesia to avoid fraud and human trafficking.Â Keywordsâ€” Android, Animation, Indonesian Worker, Interactive, MultimediaÂ